Under the sign of Capricorn : a Corto Maltese graphic novel - Pratt, Hugo (EuroComics, an imprint of IDW Publishing, 2014)
This book, the first of twelve volumes, launches the definitive English-language edition of Hugo Pratt's masterpiece, presented in the original oversized B&W format and with new translations made from Pratt's original Italian scripts... The adventures of this modern Ulysses are set during the first thirty years of the 20th Century in such exotic locales as Pratt's native Venice, the steppes of Manchuria, the Caribbean islands, the Danakil deserts, the Amazon forests, and the waves of the Pacific.